2013
DOI: 10.5267/j.msl.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the effect of advertising corporate social responsibility on building corporate reputation and brand equity

Abstract: Corporate social responsibility (CSR) plays an important role on creating a good image for business owners especially in banking industry. In this paper, we present an empirical survey to measure the impact of CSR on increasing reputation as well as creating brand equity through customer satisfaction. There are five hypotheses in our survey where we examine whether positive perception on bank's customers on CSR activities influences customer satisfaction, brand equity and firm's reputation. In addition, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…In addition, the results of our survey have been consistent with other studies performed recently on the same chain (e.g. Qaemi, 2012;Saeednia & Sohani, 2013;Azad et al, 2013;Hakkak & Zare, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the results of our survey have been consistent with other studies performed recently on the same chain (e.g. Qaemi, 2012;Saeednia & Sohani, 2013;Azad et al, 2013;Hakkak & Zare, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Brand Awareness correlated with Brand Equity of outpatient in RSIA Nun Surabaya. Suggestion in this research is improvement of marketing / promotion service so that Nun's mother and child hospital in the first time of customers mind by making leaflet and brochure (Saeednia & Sohani, 2013, Pirayesh R.,& Ghaempanah M, 2014. Battistoni et al (2013), Prominent Determinants of Consumer-Based Brand Equity.…”
Section: Resultsmentioning
confidence: 99%
“…The research found that the social features of products enhance their optimal value and helps firms to gain a competitive advantage over other companies in the industry. Saeednia and Sohani (2013) also investigated the impacts of CSR on the perception of stakeholders especially customers and it has been found in their research that companies engaged in CSR practices can improve their reputation in the industry. According to Malik and Kanwal (2018) companies are increasingly adapting the strategies which incorporate social initiatives as they have learnt that their actions are reflected in the perception of external and internal stakeholders.…”
Section: Outcomes and Disclosures Of Corporate Social Responsibilitymentioning
confidence: 99%